Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Gradient‐based habitat affinities predict species vulnerability to drought - Diane M. Debinski; Jennet C. Caruthers; Dianne Cook; Jason Crowley; Hadley Wickham (Ecology, 2013)
Ecological fingerprints of climate change are becoming increasingly evident at broad geographical scales as measured by species range shifts and changes in phenology. However, finer‐scale species‐level responses to environmental fluctuations may also provide an important bellwether of impending future community responses. Here we examined changes in abundance of butterfly species along a hydrological gradient of six montane meadow habitat types in response to drought. Our data collection began prior to the drought, and we were able to track changes for 11 years, of which eight were considered mild to extreme drought conditions. We separated the species into those that had an affinity for hydric vs. xeric habitats. We suspected that drought would favor species with xeric habitat affinities, but that there could be variations in species‐level responses along the hydrological gradient. We also suspected that mesic meadows would be most sensitive to drought conditions. Temporal trajectories were modeled for both species groups (hydric vs. xeric affinity) and individual species. Abundances of species with affinity for xeric habitats increased in virtually all meadow types. Conversely, abundances of species with affinity for hydric habitats decreased, particularly in mesic and xeric meadows. Mesic meadows showed the most striking temporal abundance trajectory: Increasing abundances of species with xeric habitat affinity were offset by decreasing or stable abundances of species with hydric habitat affinity. The one counterintuitive finding was that, in some hydric meadows, species with affinity for hydric habitats increased. In these cases, we suspect that decreasing moisture conditions in hydric meadows actually increased habitat suitability because sites near the limit of moisture extremes for some species became more acceptable. Thus, species responses were relatively predictable based upon habitat affinity and habitat location along the hydrological gradient, and mesic meadows showed the highest potential for changes in community composition. The implications of these results are that longer‐term changes due to drought could simplify community composition, resulting in prevalence of species tolerant to drying conditions and a loss of species associated with wetter conditions. We contend that this application of gradient analysis could be valuable in assessing species vulnerability of other taxa and ecosystems.

Exploring Environmental Data in a Highly Immersive Virtual Reality Environment - Dianne Cook; Carolina Cruz-Neira; Bradley D. Kohlmeyer; Uli Lechner; Nicholas Lewin; Laura Nelson; Anthony Olsen; Sue Pierson; Jürgen Symanzik (Environmental Monitoring and Assessment, 1998)